2021
DOI: 10.1097/qad.0000000000003111
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of treatment with two different interferon-alpha subtypes on HIV-1-associated T-cell activation and dysfunction in humanized mice

Abstract: Objective: Interferon-alpha (IFN-a) has been associated with excessive immune activation and dysfunction during HIV-1 infection. However, evidence suggests specific IFN-a subtypes may be beneficial rather than detrimental. This study compared the effects of treatment with two different IFN-a subtypes on indicators of T-cell activation and dysfunction during HIV-1 infection.Design: Humanized mice were infected with HIV-1 for 5 weeks and then treated with two different IFN-a subtypes for an additional 3 weeks. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 98 publications
(140 reference statements)
0
11
1
Order By: Relevance
“…In HIV-infected PBMCs the effects of IFN treatment on CD107a + T cells was even stronger compared to HIV-infected LPMCs ( Figure 1F ). In contrast to studies from HIV-infected humanized mice ( 2 , 11 ) in vitro stimulation with IFNα14 and IFNβ significantly increased percentages of CD107a-expressing CD4 + and CD8 + T cells in comparison to untreated and IFNα2-treated HIV-infected PBMCs. Similar effects were also observed in CD56 + NK cells, whereas the changes in CD107a-expressing CD56 + NK cells were not significant in LPMCs and PBMCs ( Figures 1C, F ).…”
Section: Resultscontrasting
confidence: 89%
See 3 more Smart Citations
“…In HIV-infected PBMCs the effects of IFN treatment on CD107a + T cells was even stronger compared to HIV-infected LPMCs ( Figure 1F ). In contrast to studies from HIV-infected humanized mice ( 2 , 11 ) in vitro stimulation with IFNα14 and IFNβ significantly increased percentages of CD107a-expressing CD4 + and CD8 + T cells in comparison to untreated and IFNα2-treated HIV-infected PBMCs. Similar effects were also observed in CD56 + NK cells, whereas the changes in CD107a-expressing CD56 + NK cells were not significant in LPMCs and PBMCs ( Figures 1C, F ).…”
Section: Resultscontrasting
confidence: 89%
“…The experimental data are still puzzling as the different studies showed quite opposing results. We and others have previously shown that during acute and chronic HIV infection of BLThumanized mice, IFNa14 treatment resulted in significantly reduced viremia and the treatment did not induce hyperimmune activation (2,11,12,31). During acute HIV infection treatment with IFNa2 resulted in increased frequencies of CD8 + T cells expressing cytotoxic molecules like CD107a and Granzyme B, and IFNa14 preferentially targeted NK cell responses by increasing TRAIL expression (2).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…IFN plays a vital role in the innate host antiviral response and contributes to the suppression of HIV viremia. 60 Compared to ARTsuppressed participants, NSV participants significantly down-regulated transcription of IFN genes and multiple genes involved in the IFN-response pathway (Fig. 4), including key regulators IRF3 and IRF7 (Fig.…”
Section: Discussionmentioning
confidence: 97%